Implementation and Performance Evaluation of a Digital Adjustable Voltage and Current Protection System for Off-Grid Solar Photovoltaic Applications - Lamhot Tua Situmorang; Moranain Mungkin; Syarifah Muthia Putri; Muhammad Fadlan Siregar (INFOKUM, 2026)
Off-grid Solar Photovoltaic (PV) systems are widely deployed in remote and isolated areas where access to the utility grid is unavailable. However, the reliability of these systems is often compromised by electrical disturbances, including overvoltage, undervoltage, and overcurrent conditions, which may damage inverters and connected electrical loads. This study aims to design, implement, and evaluate the performance of a Digital Adjustable Voltage and Current Protectorfor enhancing the protection of off-grid PV systems. An Adjustable AC Voltage Regulator (Variac) was employed to simulate various voltage conditions under controlled laboratory experiments, while different load levels were applied to assess the system's protection capability. The evaluated parameters included input voltage, output voltage, load current, protection status, and protection response time. Experimental results demonstrate that the proposed protection system effectively disconnects the load under undervoltage conditions at 190 VAC, overvoltage conditions at 240 VAC, and overcurrent conditions exceeding 1.15 A. Furthermore, the protection device exhibits a rapid response time ranging from 0.7 to 0.9 s, ensuring prompt isolation of abnormal operating conditions. The findings indicate that the proposed digital protection system significantly improves the operational safety, reliability, and stability of off-grid PV installations. Therefore, the developed system offers a practical and cost-effective solution for protecting standalone solar power systems, particularly in rural electrification and remote energy applications.